THE QUANTUM DOTS SOLAR CELLS BASED-ON DIFFERENT COUNTER ELECTRODES - Tung, Ha Thanh; Nguyen, Nguyen Thanh (Vietnam Journal of Science and Technology, 2015)
Solar cells based on a mesoporous structure of TiO2 and the polysulﬁde redox electrolyte were prepared by direct adsorption of CdS/CdSe/ZnS quantum dots (QDs) light absorbers onto the oxide. Moreover, we also synthesized quantum dots solar cells (QDSSCs) based on different counter electrodes like CuS, Cu2S, PbS by successive ionic layer adsorption and reaction (SILAR) method and chemical bath deposition (CBD). The performance photovoltaic was about 0.87 % for Cu2S counter electrode, i.e. higher than other counter electrodes. With this result, CuS, Cu2S and PbS exhibit several advantages in which they can replace Pt commercial in the future.